Carbon dioxide uptakes by acetylene by-products through gas–solid and gas–solid–liquid reactions. (September 2021) - El Gamal, Maisa; Mohammad, Ameera; Hameedi, Suhaib; AlZawahreh, Hadeel
Abstract: In this work, carbon dioxide uptake value by acetylene by-products was evaluated through two types of carbonation reactions. In the first reaction, solid acetylene by-products were reacted with a simulated effluent CO2 gas (10% CO2 and 90% air) and the maximum uptake value of carbon dioxide per unit mass of reacted solids was calculated. In the second reaction, the mixed solid acetylene by-product with distilled water at a specific mass to volume ratio was reacted with the same effluent CO2 gas to compare the maximum CO2 uptake value with the first reaction. It was found that a superior CO2 uptake in the case of G-S-L reaction with a value of 0.34 g CO2 /g ABP over that found in the case of G-S system of 0.14 g CO2 /g ABP . The fresh (unreacted) and treated acetylene by-products from both reactions were analyzed to study the effect of carbonation process on solids morphology, average particle size and carbon content. The structural and chemical characteristics of the fresh and carbonated acetylene by-products were investigated using X-ray diffraction, scanning electron microscopy and thermogravimetric analysis. The fresh acetylene by-products showed a major structure of portlandite crystals. All carbonated products exhibited a calcite crystal structure but with different morphology and particle size for each specific chemical reaction.